The heroic nature of the expert presenter: a practitioner's perspective. - Gough-Brady, Catherine (New Writing: The International Journal for the Practice & Theory of Creative Writing, 2022)
In this article I explore the nature of the expert presenter character, in particular the relationship between that character and the person playing the role, and also between that character and the narrative structure of the episodes they present. I use Robert McKee's separation of 'character' and 'characterization' to explore how the presenter character can perform the same actions in different series, and yet be played by different presenters. I find that the presenter is a type of hero who achieves wholeness at the end of each episode once they have 'discovered' the knowledge. However, I find that there is a unique form of the hero's journey that takes place in some presenter documentaries where the presenter hands the 'elixir' of this knowledge to the viewer to take back to their real world, rather than the presenter returning to their world with it. To understand the nature of the presenter character I use my own experience as director of presenter documentaries, interviews with presenters I have worked with, and an interview with one of the producers of the landmark BBC series Simon Schama's A History of Britain (2000–2002).